1993
DOI: 10.1091/mbc.4.11.1109
|View full text |Cite
|
Sign up to set email alerts
|

The 170-kDa glucose-regulated stress protein is an endoplasmic reticulum protein that binds immunoglobulin.

Abstract: Anoxia, glucose starvation, calcium ionophore A23187, EDTA, glucosamine, and several other conditions that adversely affect the function of the endoplasmic reticulum (ER) induce the synthesis of the glucose-regulated class of stress proteins (GRPs). The primary GRPs induced by these stresses migrate at 78 and 94 kDa (GRP78 and GRP94). In addition, another protein of -150-170 kDa (GRP170) has been previously observed and is coordinately induced with GRP78 and GRP94. To characterize this novel stress protein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(130 citation statements)
references
References 42 publications
4
126
0
Order By: Relevance
“…Less is understood at the molecular level of grp170 structure and function; however, cellular studies have shown that it binds to Ig chain in the ER, may be the ATPase responsible for protein import into the ER, and actively binds peptides from TAP (i.e., the transporter associated with Ag processing; Refs. 11,19,20,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Less is understood at the molecular level of grp170 structure and function; however, cellular studies have shown that it binds to Ig chain in the ER, may be the ATPase responsible for protein import into the ER, and actively binds peptides from TAP (i.e., the transporter associated with Ag processing; Refs. 11,19,20,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…An anti-GRP170 antibody, prepared and characterized in this laboratory [9], was used to screen a hamster 2gtl 1 expression library. Four positive clones were identified and all of their cDNAs were found to hybridize, on a Northern blot of total RNA, to an anoxia-inducible message of approximately 4 kb.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the principal members of this family, grp78 and grp94 (of 78 and 94 kDa), are resident in the endoplasmic reticulum under normal conditions and have been strongly implicated in the processing of proteins traversing the secretory pathway [4~7]. In addition to these two grps, a third grp of approximately 150 to 170 kDa has been long observed, but has only recently been characterized [9]. Biochemical analysis of grpl70 indicates that, like grp78 and grp94, it may also be involved in the processing of proteins in the secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations